Survey of Special Education Eligibility Criteria for the Category Visual Impairment Including Blindness. (March 2023) - Schles, Rachel Anne; Travers, Hilary E.
Introduction: Special education eligibility criteria vary across U.S. states; this study reports a systematic analysis of interstate eligibility criteria in the Individuals with Disabilities Education Act (IDEA) category of visual impairments including blindness.Method: Eligibility criteria for all 56 U.S. states, territories, and Washington, DC, were collected and coded on 20 different variables. Variables included use of federal language, qualifying conditions, assessment components, and eligibility team member requirements.Results: Fourteen of 56 states use similar or identical eligibility criteria written in IDEA. Forty-one states (73%) included language that specified criteria or operationally defined what it meant to be a student with a visual impairment in their state. Although about half of the states included an eye report as part of the eligibility process, few specifically mentioned functional vision, learning media, and orientation and mobility assessments in their criteria.Discussion: Significant interstate variations in the interpretation of who qualifies as a student with a visual impairment exist in the United States. Some eligibility criteria were written in an unclear language, making the criteria hard to interpret. Given that identification and prevalence rates of students with disabilities, including students with visual impairments, correlate to components of eligibility criteria, future work should seek to develop an operationalized universal definition of who qualifies as a student with visual impairment in schools.Implications for Practitioners: Since significant interstate variations exist, students, families, and educators must have easy access to all states' criteria so that families may understand how a student's eligibility for services may change if they move between states.